Biosafe catalyst, preparation method thereof and application of biosafe catalyst in ring-opening polymerization of cyclic lactone

Through the new organic zinc and organic magnesium catalysts, the activity and stability are improved by using metal-aryl oxygen bonds, the toxicity, energy consumption and cost problems of existing catalysts in the preparation of polylactic acid are solved, efficient and controllable polymerization is achieved, and high purity and safety requirements in the biomedical field are met.

CN119504803APending Publication Date: 2025-02-25QINGDAO UNIV OF SCI & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202410848631.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing catalysts have toxicity problems, high energy consumption, high production costs and poor polymerization controllability when preparing polylactic acid, which cannot meet the high purity and safety requirements in the biomedical field.

Method used

The new organic zinc and organic magnesium catalysts are used to react phenol with alkyl zinc or alkyl magnesium to form metal-aryl oxygen bonds, which improves the activity and stability of the catalyst and achieves controllable ring-opening polymerization of cyclic lactones.

Benefits of technology

It realizes a biosafety and low toxicity catalyst, simplifies the preparation process, reduces costs, and can achieve efficient polymerization under mild conditions to prepare high molecular weight aliphatic polyester to meet the requirements of medical devices and tissue engineering scaffolds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004916295940000021
    Figure BDA0004916295940000021
  • Figure BDA0004916295940000022
    Figure BDA0004916295940000022
  • Figure BDA0004916295940000031
    Figure BDA0004916295940000031
Patent Text Reader

Abstract

The invention provides a biosafety catalyst and a preparation method thereof. Controllable ring opening polymerization of various aliphatic ring lactones is realized by using the catalyst. The catalyst provided by the invention has the following beneficial effects: 1) the catalyst has good biological safety and compatibility, and the catalyst can be easily removed from an obtained polymer through a precipitation method; (2) the used organic zinc and organic magnesium catalysts are simple to prepare, convenient to implement and low in cost; 3) controllable ring-opening polymerization of a series of cyclic lactone and lactide monomers can be realized under mild conditions, and the method has strong universality; and 4) the catalyst has high activity and can be used for preparing high-molecular-weight aliphatic polyester.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a novel high-activity, biosafe catalyst, in particular to an organic zinc and organic magnesium catalyst and a preparation method thereof. The catalyst can be used for efficiently catalyzing the ring-opening polymerization of cyclic lactones. Background Art

[0002] After more than 80 years of development, synthetic polymers have become an indispensable part of our modern life. Among them, the application of biocompatible and degradable polymer materials in the medical field is of great significance. Medical polymer materials are widely used in the fields of medical devices, medical packaging and drug carriers, such as medical polylactic acid, glycolide-lactide copolymer and other polymer materials. Polylactic acid (PLA) is currently widely used in surgical sutures, tissue engineering scaffolds and medical fillers due to its good biocompatibility and degradability. The catalysts commonly used in the industrial preparation of polylactic acid are stannous octoate, Lewis acid-base catalysts and organometallic catalysts. However, organotin catalysts have strong toxicity. In 2011, the Japan Industrial Safety and Health Association conducted a test study on the toxicity of organotin. The study showed that tin has great toxicity to organisms, which limits its application in the medical field (Jo occup Health, 2011, 53 (2): 51-63). Lewis acid-base catalysts require higher temperatures or pressures to achieve the same catalytic efficiency as organometallic catalysts, which increases energy consumption and production costs, and cannot be used to prepare high molecular weight polyesters. Organic aluminum catalysts have low toxicity, but still cannot meet the higher level of purity and safety requirements in the field of implantable medical devices. Metallic zinc (Zn) is a trace element necessary for the human body, so the polylactic acid material obtained with organic zinc as a catalyst not only has excellent biocompatibility and degradability, but is also non-toxic and harmless to the human body. Metallic magnesium (Mg) is the fourth most abundant trace element in the human body. Harbin Medical University has conducted research on the toxicity of metallic magnesium to organisms, and the results show that trace magnesium elements are non-toxic to organisms (Oral Medicine, 2023, 43 (10): 878-882). In 2010, S. Sirol of Futro Company in Belgium applied for a patent (CN102639599B) containing an organic zinc catalyst ((2,4-di-tert-butyl-6-(((2-(dimethylamino)ethyl)(methyl)amino)methyl)phenoxy)(ethoxy)zinc), and used this catalyst to prepare polylactic acid. However, the polymerization controllability of the catalyst is poor, resulting in unsatisfactory molecular weight and performance of the prepared polylactic acid. More importantly, the synthesis of the organozinc catalyst is complex, and the synthesis of the ligand in particular requires complicated steps, and the catalyst preparation is cumbersome and costly, which hinders its practical application. And other simple organozinc catalysts, such as diethylzinc and zinc octoate, are used to catalyze the molecular weight of the polymer prepared when ring-opening polymerization of cyclic lactones is much lower than the theoretical value, and it is impossible to obtain a high molecular weight polymer (J.Polym Sci.2022,60(23):3222-3231).In 2021, the Qingdao Institute of Bioenergy and Process Technology of the Chinese Academy of Sciences applied for a patent containing an organic magnesium catalyst (bis(hexamethyldisilazane)magnesium) (CN113698584A). Although this organic magnesium catalyst has a simple structure, it is unstable. Bis(hexamethyldisilazane)magnesium will be deactivated or decomposed under water, oxygen and high temperature conditions, resulting in a decrease in catalytic activity. In addition, the synthesis cost of bis(hexamethyldisilazane)magnesium is relatively high, which is not conducive to large-scale production and wide application.

[0003] In order to overcome these problems, the present invention provides a class of biosafe novel organic zinc and organic magnesium catalysts to achieve controlled ring-opening polymerization of cyclic lactones and prepare biocompatible aliphatic polyesters, which can meet the requirements of biomedicine. The organic zinc and organic magnesium catalysts provided by the present invention utilize phenol to react with alkyl zinc or alkyl magnesium to generate metal-aryl oxygen bonds, which can well stabilize the metal active center, thereby improving the activity and stability of the catalyst.

[0004] The novel organic zinc and organic magnesium catalysts provided by the present invention have the following advantages: 1) Zn and Mg are trace elements necessary for the human body, and the toxicity of the prepared organic zinc and organic magnesium catalysts is much lower than that of other metal catalysts currently reported, and they have good biosafety and compatibility; 2) The preparation of the used organic zinc and organic magnesium catalysts is simple, easy to implement and low in cost; 3) the controlled ring-opening polymerization of a series of cyclic lactone and lactide monomers can be achieved under mild conditions, with strong universality, and the catalyst can be easily removed from the obtained polymer by precipitation; 4) the catalyst has high activity and can prepare high molecular weight aliphatic polyester, and the mechanical properties of the obtained polyester can meet the requirements of medical devices and tissue engineering scaffolds. Summary of the invention

[0005] The present invention provides a novel biosafe organic zinc and organic magnesium catalyst having a structure as shown in formula (I) or formula (II):

[0006]

[0007] Wherein R1 is an alkyl group or an aryloxy group; R2 is an aryloxy group;

[0008] Preferably, the alkyl group is methyl, ethyl, propyl or butyl; the aryloxy group has the structure shown in formula (III):

[0009]

[0010] Wherein R3, R4, and R5 are hydrogen or an alkyl group having 1 to 4 carbon atoms.

[0011] The present invention also provides a method for preparing the above-mentioned organic zinc and organic magnesium catalysts, comprising the following steps:

[0012] (1) mixing alkyl zinc or alkyl magnesium with phenol or substituted phenol under a nitrogen atmosphere and stirring;

[0013] (2) draining the solvent from the mixture to obtain a powdered organic zinc or organic magnesium catalyst;

[0014] In the above preparation method, the molar ratio of alkyl zinc or alkyl magnesium to phenol or substituted phenol is 1 / 1 or 1 / 2.

[0015] Another object of the present invention is to provide a method for preparing aliphatic poly(thio)esters by using the above-mentioned organozinc and organomagnesium catalysts to catalyze the controlled ring-opening polymerization of cyclic monomers, comprising the following steps:

[0016] (1) dissolving an initiator and an organozinc or organomagnesium catalyst in an organic solvent and stirring at room temperature for 5 to 30 minutes;

[0017] (2) adding the cyclic monomer to the mixed solution, reacting at -40 to 200° C. for 10 min to 8 h to obtain a polymer;

[0018] In the above preparation method, the cyclic monomer is γ-butyrolactone, δ-valerolactone, δ-thiovalerolactone, α-methylene-δ-valerolactone, β-methyl-δ-valerolactone, δ-caprolactone, lactide, glycolide, ε-caprolactone, 1,4-dioxane-2-one, 1,5-dioxepane-2-one, enantholactone, twelve-membered ring lactone, thirteen-membered ring lactone, sixteen-membered ring lactone, seventeen-membered ring lactone or a mixture of the above cyclic monomers. The cyclic monomer has one of the following structures:

[0019]

[0020] In the above preparation method, the initiator is one of methanol, ethanol, isopropanol, tert-butanol, benzyl alcohol, phenylethyl alcohol, phenylpropyl alcohol, 2,2-diphenylethyl alcohol, ethylene glycol, 1,4-phenyldimethanol, glycerol, and pentaerythritol; the molar ratio of the initiator to the catalyst is 1 / 1 to 100 / 1;

[0021] In the above preparation method, the organic solvent is toluene, tetrahydrofuran, dichloromethane, acetonitrile or chloroform.

[0022] In the above preparation method, the molar concentration of the cyclic monomer in the system is 2 to 13 mol / L; the molar ratio of the initiator to the cyclic monomer is 1 / 10 to 1 / 5000. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The prepared organic zinc catalyst (Zn-2) of 1 H NMR spectrum.

[0024] Figure 2 The obtained organic magnesium catalyst (Mg-3) of 1 H NMR spectrum.

[0025] Figure 3 The molecular weight of the poly(L-lactide) prepared in Comparative Example 1 varies with feed ratio.

[0026] Figure 4 This is the GPC spectrum of the poly(ε-caprolactone) prepared in Comparative Example 2.

[0027] Figure 5 The molecular weight of the poly(ε-caprolactone) prepared in Comparative Example 2 varies with feed ratio.

[0028] Figure 6 The molecular weight of the poly(L-lactide) prepared in Example 2 varies with feed ratio.

[0029] Figure 7 The molecular weight of the poly(ε-caprolactone) prepared in Example 5 varies with the feed ratio.

[0030] Figure 8 This is the GPC spectrum of the poly(ε-caprolactone) prepared in Example 6. DETAILED DESCRIPTION

[0031] The present invention is described in detail with reference to the following embodiments, but the present invention is not limited to these embodiments.

[0032] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0033] Comparative Example 1

[0034] Benzyl alcohol (0.01mmol, 1.04uL) and diethyl zinc (0.01mmol, 1.24mg) were added to 5 reaction tubes respectively, and then different amounts of L-lactide (1mmol, 5mmol, 10mmol, 20mmol, 30mmol) were added to 5 reaction tubes respectively (i.e., the ratio of monomer to initiator was 100 / 1, 500 / 1, 1000 / 1, 2000 / 1, 3000 / 1). The reaction was carried out at 150°C under nitrogen protection for 3h. The reaction mixture was dissolved in 5mL of dichloromethane, then poured into 50mL of methanol, and the polymer was obtained by centrifugal separation and precipitation. The molecular weight changes with the feed ratio as shown in Figure 3 The data of 5 polymer samples measured by GPC are shown in the following table, among which no polymer was precipitated when M / C / I=3000 / 1 / 1, indicating that the monomer conversion rate is very low:

[0035]

[0036] Comparative Example 2

[0037] (0.01mmol, 1.04uL) benzyl alcohol, (0.01mmol, 10uL) di-n-butyl magnesium and 1.433mL of THF were added to 4 reaction tubes respectively, stirred at 25°C for 10min, and then different amounts of ε-caprolactone (2mmol, 5mmol, 10mmol, 20mmol) were added to 4 reaction tubes respectively (i.e. the ratio of monomer to initiator was 200 / 1, 500 / 1, 1000 / 1, 2000 / 1 respectively). The reaction was carried out at 25°C under nitrogen protection for 30min. The reaction mixture was dissolved in 5mL of dichloromethane, then poured into 50mL of methanol, and centrifuged to separate and precipitate to obtain a polymer. The GPC spectrum of the polymer obtained in Run 3 is shown in FIG. Figure 4 As shown in Figure 2, the molecular weight changes with the feed ratio. Figure 5 The data of 5 polymer samples measured by GPC are shown in the figure below:

[0038]

[0039] Comparative Example 3

[0040] Benzyl alcohol (0.01mmol, 1.04uL) and diethyl zinc (0.01mmol, 1.24mg) were dissolved in 1.433mL of THF, stirred at 25°C for 10min, and then ε-caprolactone (10mmol, 1.068mL) was added to the reaction tube with a syringe and stirred. The reaction was carried out under nitrogen protection for 8h. The reaction mixture was dissolved in 3mL of dichloromethane, then poured into 50mL of methanol, and centrifuged to precipitate to obtain a polymer. The number average molecular weight measured by GPC was 62.3kg / mol, and the molecular weight distribution was 1.67.

[0041] Example 1

[0042] (30mmol, 3.71g) diethylzinc and (30mmol, 6.61g) 2,6-di-tert-butyl-p-methylphenol were added to a 25mL eggplant-shaped bottle, and 10mL of n-hexane was added as solvent. After stirring for 2h at room temperature under nitrogen atmosphere, the solvent was drained to obtain a white powdery organic zinc catalyst. The organic zinc catalyst obtained by NMR characterization is the target catalyst Zn-2, and its NMR hydrogen spectrum is as follows Figure 1 shown.

[0043] Example 2

[0044] Benzyl alcohol (0.01mmol, 1.04uL) and Zn-2 (0.01mmol, 3.1mg) were added to 5 reaction tubes respectively, and then different amounts of L-lactide (2mmol, 5mmol, 10mmol, 20mmol, 30mmol) were added to 5 reaction tubes respectively (i.e. the ratio of monomer to initiator was 100 / 1, 500 / 1, 1000 / 1, 2000 / 1, 3000 / 1). The reaction was carried out at 150°C under nitrogen protection for 3h. The reaction mixture was dissolved in 5mL of dichloromethane, then poured into 50mL of methanol, and the polymer was obtained by centrifugal separation and precipitation. The molecular weight changes with the feed ratio as shown in Figure 6 The data of 5 polymer samples measured by GPC are shown in the following table:

[0045]

[0046] Compared with the diethyl zinc catalyst (Comparative Example 1), Zn-2 has higher polymerization activity and more controllable reaction. When diethyl zinc is used as a catalyst, when the ratio of monomer to initiator is greater than 1000 / 1, the molecular weight increases slowly and is much less than the theoretical molecular weight, and the molecular weight does not change linearly with the feed ratio, indicating that the polymerization is uncontrollable, and the monomer conversion rate is very low when M / C / I=3000 / 1 / 1, indicating that the catalyst activity and stability are poor; while Zn-2 still has higher catalytic activity when the ratio of monomer to initiator is 3000 / 1, and the monomer conversion rate is high. In addition, the polymer molecular weight increases linearly with the feed ratio, indicating that the polymerization is more controllable.

[0047] Example 3

[0048] (0.01mmol, 1.04uL) benzyl alcohol, (0.01mmol, 3.1mg) Mg-3, (10mmol, 1.44g) L-lactide were added to a reaction tube under N2 atmosphere and reacted at 150°C for 3h. After the reaction, it was dissolved with dichloromethane and then poured into 50mL methanol. The polymer was separated by centrifugation and precipitated to obtain a polymer. The number average molecular weight measured by GPC was 59.8kg / mol and the molecular weight distribution was 1.54.

[0049] Example 4

[0050] (0.01mmol, 1.04uL) benzyl alcohol, (0.01mmol, 3.1mg) Mg-3, (20mmol, 1.44g) L-lactide were added to a reaction tube under N2 atmosphere and reacted at 150°C for 3h. After the reaction, it was dissolved with dichloromethane and then poured into 50mL methanol. The polymer was separated by centrifugation and precipitated to obtain a polymer. The number average molecular weight measured by GPC was 79.6kg / mol and the molecular weight distribution was 1.47.

[0051] Example 5

[0052] Add (0.01mmol, 1.04uL) benzyl alcohol, (0.01mmol, 3mg) Mg-3 and 1.433mL THF to 4 reaction tubes respectively, stir at 25℃ for 10min, then add different amounts of ε-caprolactone (2mmol, 5mmol, 10mmol, 20mmol) to 4 reaction tubes respectively (i.e. the ratio of monomer to initiator is 200 / 1, 500 / 1, 1000 / 1, 2000 / 1 respectively). The reaction was carried out at 25℃ and under nitrogen protection for 30min. The reaction mixture was dissolved in 5mL dichloromethane, then poured into 50mL methanol, and the polymer was obtained by centrifugation and precipitation. The molecular weight changes with the feed ratio as shown in Figure 7 The data of 5 polymer samples measured by GPC are shown in the figure below:

[0053]

[0054] Compared with di-n-butyl magnesium catalyst (Comparative Example 2), Mg-3 has higher polymerization activity and more controllable reaction. When di-n-butyl magnesium is used as catalyst, when the ratio of monomer to initiator is greater than 500 / 1, the molecular weight increases slowly and is far less than the theoretical molecular weight value, and the molecular weight does not change linearly with the feed ratio; when Mg-3 is used as catalyst, when the ratio of monomer to initiator is from 200 / 1 to 2000 / 1, the molecular weight increases linearly with the feed ratio, which is closer to the theoretical molecular weight, indicating that the polymerization is more controllable.

[0055] Example 6

[0056] Dissolve (0.01mmol, 1.04uL) benzyl alcohol and (0.01mmol, 3.1mg) Zn-2 in 1.433mL THF, stir at 25℃ for 10min, then add (10mmol, 1.068mL) ε-caprolactone into the reaction tube with a syringe and stir. The reaction was carried out for 3h under nitrogen protection. The reaction mixture was dissolved in 3mL dichloromethane and then poured into 50mL methanol. The polymer was separated and precipitated by centrifugation. The number average molecular weight measured by GPC was 89.0kg / mol, and the molecular weight distribution was 1.40. The GPC spectrum is shown in Figure 8 Compared with a single alkyl zinc catalyst (Comparative Example 3), Zn-2 has higher polymerization activity, shorter reaction time, and a molecular weight increased to 90,000 with a narrower distribution.

[0057] Example 7

[0058] (0.02mmol, 2.08uL) benzyl alcohol and (0.01mmol, 3.1mg) Zn-2 were dissolved in 578uL THF, stirred at 25°C for 10min, and then (4mmol, 400mg) δ-valerolactone was added to the reaction tube with a syringe and stirred. The reaction was carried out for 10min under nitrogen protection. The reaction mixture was dissolved in 3mL dichloromethane, then poured into 50mL methanol, and centrifuged to precipitate to obtain a polymer. The number average molecular weight measured by GPC was 37.3kg / mol, and the molecular weight distribution was 1.45.

[0059] Example 8

[0060] (0.02mmol, 2.08uL) benzyl alcohol and (0.01mmol, 3.0mg) Mg-3 were dissolved in 578uL THF, stirred at 25°C for 10min, and then (4mmol, 400mg) δ-valerolactone was added to the reaction tube with a syringe and stirred. The reaction was carried out for 10min under nitrogen protection. The reaction mixture was dissolved in 3mL dichloromethane, then poured into 50mL methanol, and centrifuged to precipitate to obtain a polymer. The number average molecular weight measured by GPC was 37.9kg / mol, and the molecular weight distribution was 1.51.

[0061] Example 9

[0062] (0.02mmol, 2.08uL) benzyl alcohol and (0.01mmol, 3.0mg) Mg-3 were dissolved in 578uL THF, stirred at 25°C for 10min, and then (4mmol, 464mg) δ-thiovalerolactone was added to the reaction tube with a syringe and stirred. The reaction was carried out under nitrogen protection for 10min. The reaction mixture was dissolved in 3mL dichloromethane, then poured into 50mL methanol, and centrifuged to precipitate to obtain a polymer. The number average molecular weight measured by GPC was 25.6kg / mol, and the molecular weight distribution was 1.62.

[0063] Example 10

[0064] (0.01mmol, 1.04uL) benzyl alcohol, (0.01mmol, 3.1mg) Zn-5 Dissolve in 2.5 mL of THF, stir at 25 ° C for 10 min, then add (10 mmol, 861 mg) of γ-butyrolactone to the reaction tube with a syringe and stir. The reaction was carried out at -40 ° C under nitrogen protection for 3 h. The reaction mixture was dissolved in 3 mL of dichloromethane, then poured into 50 mL of methanol, and centrifuged to precipitate to obtain a polymer. The number average molecular weight measured by GPC was 64.7 kg / mol, and the molecular weight distribution was 1.25.

[0065] Embodiment 11

[0066] (0.01mmol, 1.36mg) phenylpropanol, (0.01mmol, 3.1mg) Zn-7 Dissolve in 2.5 mL of THF, stir at 25 ° C for 10 min, then add (10 mmol, 1.58 g) of α-methylene-δ-valerolactone to the reaction tube with a syringe and stir. The reaction was carried out for 3 h under nitrogen protection. The reaction mixture was dissolved in 3 mL of dichloromethane, then poured into 50 mL of methanol, and centrifuged to precipitate to obtain a polymer. The number average molecular weight measured by GPC was 113.7 kg / mol, and the molecular weight distribution was 1.32.

[0067] Example 12

[0068] (0.01 mmol, 1.40 mg) 1,4-phenyl dimethanol, (0.01 mmol, 3.1 mg) Zn-8 Dissolve in 2.5 mL of THF, stir at 25 ° C for 10 min, then add (10 mmol, 1.0 g) of β-methyl-δ-valerolactone to the reaction tube with a syringe and stir. The reaction was carried out for 3 h under nitrogen protection. The reaction mixture was dissolved in 3 mL of dichloromethane, then poured into 50 mL of methanol, and centrifuged to precipitate to obtain a polymer. The number average molecular weight measured by GPC was 78.6 kg / mol, and the molecular weight distribution was 1.23.

[0069] Embodiment 13

[0070] (0.01 mmol, 0.92 mg) glycerol, (0.01 mmol, 3.1 mg) Zn-9 Dissolve in 2.5 mL of THF, stir at 25°C for 10 min, then add (10 mmol, 1.16 g) glycolide into the reaction tube with a syringe and stir. The reaction was carried out under nitrogen protection for 3 h to obtain a polymer. Due to the poor solubility of polyglycolide in the solvent, GPC test was not performed.

[0071] Embodiment 14

[0072] (0.01 mmol, 1.36 mg) pentaerythritol, (0.01 mmol, 3.1 mg) Zn-10 Dissolve in 2.5 mL of THF, stir at 25°C for 10 min, then add (10 mmol, 1.02 g) of 1,4-dioxane-2-one into the reaction tube with a syringe and stir. The reaction was carried out under nitrogen protection for 3 h to obtain a polymer, which had poor solubility and was not tested by GPC.

[0073] Embodiment 15

[0074] (0.01 mmol, 1.40 mg) 1,4-phenyl dimethanol, (0.01 mmol, 3.1 mg) Mg-1 Dissolve in 2.5 mL of THF, stir at 25 °C for 10 min, then add (10 mmol, 1.16 g) 1,5-dioxepan-2-one into the reaction tube with a syringe and stir. The reaction was carried out for 3 h under nitrogen protection. The reaction mixture was dissolved in 3 mL of dichloromethane, then poured into 50 mL of methanol, and centrifuged to precipitate to obtain a polymer. The number average molecular weight measured by GPC was 76.2 kg / mol, and the molecular weight distribution was 1.47.

[0075] Example 16

[0076] (0.01mmol, 1.04uL) benzyl alcohol, (0.01mmol, 3.1mg) Mg-2 Dissolve in 2.5 mL of THF, place at 25 ° C and stir for 10 min, then add (10 mmol, 1.28 g) of enantholactone to the reaction tube with a syringe and stir. The reaction is carried out under nitrogen protection for 10 min. The reaction mixture is dissolved in 3 mL of dichloromethane, then poured into 50 mL of methanol, and centrifuged to precipitate to obtain a polymer. The number average molecular weight measured by GPC is 82.8 kg / mol, and the molecular weight distribution is 1.32.

[0077] Embodiment 17

[0078] (0.01mmol, 1.04uL) benzyl alcohol, (0.01mmol, 3.1mg) Mg-4 Dissolve in 2.5 mL of THF, stir at 25 ° C for 10 min, then add (10 mmol, 1.84 g) of 12-membered ring lactone to the reaction tube with a syringe and stir. The reaction was carried out under nitrogen protection for 10 min. The reaction mixture was dissolved in 5 mL of dichloromethane, then poured into 50 mL of methanol, and centrifuged to precipitate to obtain a polymer. The number average molecular weight measured by GPC was 112.4 kg / mol, and the molecular weight distribution was 1.53.

[0079] Embodiment 18

[0080] (0.01 mmol, 1.36 mg) phenylpropanol, (0.01 mmol, 3.1 mg) Mg-5 Dissolve in 2.5 mL of THF, stir at 25 ° C for 10 min, then add (10 mmol, 2.4 g) of 16-membered ring lactone to the reaction tube with a syringe and stir. The reaction was carried out under nitrogen protection for 10 min. The reaction mixture was dissolved in 5 mL of dichloromethane, then poured into 50 mL of methanol, and centrifuged to precipitate to obtain a polymer. The number average molecular weight measured by GPC was 132.5 kg / mol, and the molecular weight distribution was 1.53.

[0081] Embodiment 19

[0082] (0.01mmol, 1.04uL) benzyl alcohol, (0.01mmol, 3.1mg) Mg-6 Dissolve in 2.5 mL of THF, stir at 25 ° C for 10 min, then add (10 mmol, 2.54 g) of 17-membered ring lactone to the reaction tube with a syringe and stir. The reaction was carried out under nitrogen protection for 10 min. The reaction mixture was dissolved in 5 mL of dichloromethane, then poured into 50 mL of methanol, and centrifuged to precipitate to obtain a polymer. The number average molecular weight measured by GPC was 137.2 kg / mol, and the molecular weight distribution was 1.46.

Claims

1. A class of biosafe organic zinc and organic magnesium catalysts having a structure as shown in formula (I) or formula (II): Wherein R1 is an alkyl group or an aryloxy group; R2 is an aryloxy group.

2. The catalyst according to claim 1, characterized in that The alkyl group is methyl, ethyl, propyl or butyl; the aryloxy group has a structure shown in formula (III), Wherein R3, R4, and R5 are hydrogen or an alkyl group having 1 to 4 carbon atoms.

3. The method for preparing the catalyst according to claim 1, comprising the steps of: (1) mixing alkyl zinc or alkyl magnesium with phenol or substituted phenol under a nitrogen atmosphere and stirring; (2) draining the solvent from the mixture to obtain a powdered organic zinc or organic magnesium catalyst; In the above preparation method, the molar ratio of alkyl zinc or alkyl magnesium to phenol or substituted phenol is 1 / 1 or 1 / 2.

4. A method for preparing aliphatic poly(thio)esters by using the catalyst according to claim 1 to catalyze the controlled ring-opening polymerization of cyclic monomers, comprising the following steps: (1) dissolving an initiator and an organozinc or organomagnesium catalyst in an organic solvent and stirring at room temperature for 5 to 30 minutes; (2) Add the cyclic monomer to the above mixed solution and react at -40 to 200°C for 10 minutes to 8 hours to obtain a polymer.

5. The method according to claim 4, characterized in that The cyclic monomer is at least one of γ-butyrolactone, δ-valerolactone, δ-thiovalerolactone, α-methylene-δ-valerolactone, β-methyl-δ-valerolactone, δ-caprolactone, lactide, glycolide, ε-caprolactone, 1,4-dioxane-2-one, 1,5-dioxepane-2-one, heptane ester, twelve-membered ring lactone, thirteen-membered ring lactone, sixteen-membered ring lactone, and seventeen-membered ring lactone.

6. The method according to claim 4, characterized in that The initiator is one of methanol, ethanol, isopropanol, tert-butyl alcohol, benzyl alcohol, phenylethyl alcohol, phenylpropyl alcohol, 2,2-diphenylethyl alcohol, ethylene glycol, 1,4-phenyl dimethanol, glycerol and pentaerythritol.

7. The method according to claim 4, characterized in that The molar ratio of the initiator to the catalyst is 1 / 1 to 100 / 1; the molar ratio of the initiator to the cyclic monomer is 1 / 10 to 1 / 5000.

8. The method according to claim 4, characterized in that The organic solvent is toluene, tetrahydrofuran, dichloromethane, acetonitrile or chloroform; the molar concentration of the cyclic monomer in the system is 2-13 mol / L.

Citation Information

Patent Citations

  • Method for bulk polymerization of lactide

    CN102639599B

  • Method for catalyzing ring-opening polymerization of lactide and analogues thereof by magnesium catalytic system

    CN113698584A

  • Preparation of high molecular weight polylactides

    CA923245A

  • Metallic alkoxy complex, catalyst composition and preparation method of poly-caprolactone or poly-lactide

    CN102491874A

  • Aryloxy magnesium compound, preparation method, ring-opening polymerization catalyst and application thereof

    CN109796476A